A fuzzy-MADM based approach for site selection of offshore wind farm in busy waterways in China. (15th November 2018) - Wu, Bing; Yip, Tsz Leung; Xie, Lei; Wang, Yang
Abstract: The offshore wind farm has developed fast as a type of abundant, clean, renewable energy sources. The offshore wind farm located close to the shore especially in busy waterways may have significantly impact on the maritime safety. This paper proposes a fuzzy-MADM (multiple attribute decision-making) method for site selection of the offshore wind farm by comprehensively considering the feasibility of installation (i.e. cost and production) and maritime safety. The kernel of this approach is to establish a three-layer decision-making framework after identifying the influencing factors from previous works, to derive the decision matrix by integrating the influencing factor and to obtain the weights of the attributes by using the Analytic Hierarchy Process. The proposed approach is applied to a real site selection of offshore wind farm in the Eastern China Sea. The result is reasonable because it agrees with the discussion of a workshop and further analysis. Moreover, it illustrates that the maritime safety is a predominant factor for selection of offshore wind farm. Consequently, this paper provides a practical and quantitative tool for site selection of offshore wind farm. Highlights: Fuzzy-MADM is applied for offshore wind farm in busy waterways. The feasibility of installation and maritime safety are comprehensively considered. A three-layer decision making framework is established for site selection.